A Jacobian-Free Newton Krylov Implicit-Explicit Time Integration Method for Incompressible Flow Problems - Kadioglu, Samet Y.; Knoll, Dana A. (GLOBAL SCIENCE PRESS, 2013)
We have introduced a fully second order IMplicit/EXplicit (IMEX) time integration technique for solving the compressible Euler equations plus nonlinear heat conduction problems (also known as the radiation hydrodynamics problems) in Kadioglu et al., J. Comp. Physics [22, 24]. In this paper, we study the implications when this method is applied to the incompressible Navier-Stokes (N-S) equations. The IMEX method is applied to the incompressible flow equations in the following manner. The hyperbolic terms of the flow equations are solved explicitly exploiting the well understood explicit schemes. On the other hand, an implicit strategy is employed for the non-hyperbolic terms. The explicit part is embedded in the implicit step in such a way that it is solved as part of the non-linear function evaluation within the framework of the Jacobian-Free Newton Krylov (JFNK) method [8, 29, 31]. This is done to obtain a self-consistent implementation of the IMEX method that eliminates the potential order reduction in time accuracy due to the specific operator separation. We employ a simple yet quite effective fractional step projection methodology (similar to those in [11,19,21,30]) as our preconditioner inside the JFNK solver. We present results from several test calculations. For each test, we show second order time convergence. Finally, we present a study for the algorithm performance of the JFNK solver with the new projection method based preconditioner.
Keywords: Incompressible flow; Navier-Stokes equations; IMEX method; JFNK method; preconditioner; COUPLED LEVEL SET; OF-FLUID METHOD; EFFICIENT IMPLEMENTATION; PROJECTION METHOD; RADIATION; Physics